QTL mapping provides new insights into emamectin benzoate resistance in salmon lice, Lepeophtheirus salmonis - Armin Sturm; Greta Carmona-Antoñanzas; Joseph L. Humble; Claudia Croton; Sally Boyd; Rapule Mphuti; John B. Taggart; David I. Bassett; Ross D. Houston; Karim Gharbi; James E. Bron; Michaël Bekaert (BMC Genomics)
Abstract Background The salmon louse (Lepeophtheirus salmonis) is a parasite of wild and farmed salmonid fish, causing huge economic damage to the commercial farming of Atlantic salmon (Salmo salar) in the northern hemisphere. The avermectin emamectin benzoate (EMB) is widely used for salmon delousing. While resistance to EMB is widespread in Atlantic populations of L. salmonis, the molecular mechanisms of resistance remain to be elucidated. The aim of the present work was to obtain insights into potential EMB resistance mechanisms by identifying genetic and transcriptomic markers associated with EMB resistance. Results Crosses were performed between EMB-susceptible and -resistant L. salmonis, sourced from two parental strains isolated in Scotland, producing fully pedigreed families. The EMB susceptibility of individual parasites was characterised using time-to-response bioassays. Parasites of two families were subjected to double digest restriction site-associated DNA sequencing (ddRAD-seq) for simultaneous discovery of single nucleotide polymorphisms (SNPs) and genotyping. Data analysis revealed that EMB resistance is associated with one quantitative trait locus (QTL) region on L. salmonis chromosome 5. Marker-trait association was confirmed by genotyping assays for 7 SNPs in two additional families. Furthermore, the transcriptome of male parasites of the EMB-susceptible and -resistant L. salmonis parental strains was assessed. Among eighteen sequences showing higher transcript expression in EMB-resistant as compared to drug-susceptible lice, the most strongly up-regulated gene is located in the above QTL region and shows high homology to β spectrin, a cytoskeleton protein that has roles in neuron architecture and function. Further genes differentially regulated in EMB-resistant lice include a glutathione S-transferase (GST), and genes coding for proteins with predicted roles in mitochondrial function, intracellular signalling or transcription. Conclusions Major determinants of EMB resistance in L. salmonis are located on Chromosome 5. Resistance can be predicted using a limited number of genetic markers. Genes transcriptionally up-regulated in EMB resistant parasites include a β spectrin, a cytoskeletal protein with still incompletely understood roles in neuron structure and function, as well as glutathione S-transferase, an enzyme with potential roles in the biochemical defence against toxicants.